Aging and recurrent urinary tract infections are associated with bladder dysfunction in type 2 diabetes - Tzu-Li Lin; Gin-Den Chen; Yi-Ching Chen; Chien-Ning Huang; Soo-Cheen Ng (Elsevier, 2012)
Objective: The objective of this study was to demonstrate the diversity of urodynamic findings and temporal effects on bladder dysfunction in diabetes as well as to evaluate the predisposing factors that attenuate the storage and voiding function of diabetic women. Material and Methods: In this prospective study, 181 women with type 2 diabetes mellitus (DM) and lower urinary tract dysfunction underwent complete urogynecological evaluations and urodynamic studies. The patients' histories of DM and the treatment agents used were documented from chart records and interviews. The urodynamic diagnoses were recategorized into two groups for comparison, namely overactive detrusor (detrusor overactivity and/or increased bladder sensation as well as mixed incontinence) and voiding dysfunction (detrusor hyperactivity with insufficient contractility and detrusor underactivity with poor voiding efficiency) in order to evaluate the temporal effect of DM on diabetic bladder dysfunction. Results: The development of bladder dysfunction showed a trend involving time-dependent progression, beginning with storage problems (i.e. advancing from urodynamic stress incontinence to detrusor overactivity and/or increased bladder sensation) and eventually led to impaired voiding function. The duration of DM relative to the urodynamic diagnoses of these women was longer in women with voiding dysfunction (6.8 ± 2.8 years with urodynamic stress incontinence, 7.3 ± 6.5 years with detrusor overactivity and/or increased bladder sensation, and 10.4 ± 8.3 years with women with voiding dysfunction). Notwithstanding these findings, stepwise logistic regression analysis indicated that age and recurrent urinary tract infections were the two independent factors associated with developing voiding dysfunction. Conclusion: The urodynamic study revealed a temporal effect on bladder function, and women with diabetic voiding dysfunction were found to have had a longer duration of DM than women with an overactive detrusor. However, aging and recurrent urinary tract infections are the two independent factors that contribute to impaired voiding function and diabetic bladder dysfunction.